Enhanced drug metabolism in young children with cystic fibrosis. Issue 3 (1st September 1997) - Parker, A C; Pritchard, P; Preston, T; Smyth, R L; Choonara, I
Abstract : The effect of cystic fibrosis on caffeine metabolism was studied in young children using the caffeine breath test. Eight children with cystic fibrosis aged 2–6 years and nine age matched controls were studied on a single occasion, and the cumulative percentage of labelled caffeine exhaled as carbon dioxide measured over two hours. This was significantly higher in the patients with cystic fibrosis than in controls, suggesting an increase in the CYP1A2 metabolic pathway in the former. The fact that these were young children with minimal lung and liver disease suggests that enhanced drug metabolism in children with cystic fibrosis is hereditary rather than secondary to lung and liver damage.